Evolution and statistics of thermal plumes in tilted turbulent convection. (August 2017) - Guo, Shuang-Xi; Zhou, Sheng-Qi; Qu, Ling; Cen, Xian-Rong; Lu, Yuan-Zheng
Highlights: Thermal plumes are extracted from the shadowgraph images. Plume width is log-normally distributed in space and has similar scale with the thermal boundary layer thickness. Image-induced plume area density quantitatively represents the global heat flux. Plume velocity map is compared with that of the two-dimensional convective flow. Abstract: We present a systematic experimental study of thermal plumes within tilted turbulent thermal convection using the shadowgraph technique. The measurements are performed in a rectangular cell (aspect ratio Γ x = 1 and Γ y = 0.25 ) over a wide range of tilt angles ( 0 ⩽ β ⩽ π / 2  rad) at constant Prandtl ( Pr ≃ 10 ) and Rayleigh ( Ra ≃ 6.80 × 10 10 ) numbers. It is found that the plume width, λ, is distributed log-normally in space and the time-averaged most probable plume width, 〈 λ p 〉, has similar scale with the thermal boundary layer thickness, λ T . 〈 λ p 〉 and λ T slowly increase as tilt angle, β, increases from 0 to 1 rad and they broaden rapidly as β > 1  rad. The average plume area density, 〈 Φ 〉, deduced from the image intensity, is proposed to represent the heat flux of thermal plumes. Its β dependence is consistent with that of the Nusselt number, Nu, over the tilt angle range. λ p and Φ exhibit oscillation of convective flow. The oscillation intensity and period strongly depend on β, but are less affected by Ra and Pr . The plume velocity exhibits a different pattern from that of the two-dimensional convective flow measured at Pr ≃ 6.3 and Ra ≃ 4.42 × 10 9 . The magnitude of plume velocity peak is weakly affected by the cell tilting. The position of the plume velocity peak increases linearly with increasing β .